Reshaping food systems: The imperative of inclusion - Fan, Shenggen; Swinnen, Johan (International Food Policy Research Institute, 2020)
Redesigning food systems to be inclusive of poor and vulnerable people is a moral imperative. KEY FINDINGS - Inclusive food systems can help break the intergenera-tional cycle of poverty, hunger, and malnutrition. - Including marginalized people in food systems can help them secure well-paying jobs and make gains in other areas that impact long-term livelihoods, such as education. - A value chain framework is key to designing inclusive food systems—from improving farmers’ access to resources and information to creating off-farm jobs and enterprises in the midstream of the chain. - Recent innovations such as mobile phone technologies offer opportunities for marginalized and excluded populations to access information and services, and to participate all along the food value chain. - Education is a major driver of inclusion, increasing life-long income and improving nutrition, health, civic engagement, and gender equality. - Marginalized people should be empowered to make strategic choices within food systems and have a voice in holding governments accountable for delivery of inclusive food systems.